Educational program on prevention of oral health in children under the age of five - Cervantes, Sheyla (2020)
The objective of the research was to improve the level of knowledge of preventive techniques in oral health through the Educational Program called "Healthy mouths, happy faces" in children under 5 in vulnerable situations in Puno (Peru). Study was experimental, longitudinal and prospective with pre and posttest using educational and communicative method. The simplified Greene-Vermillion index and a validated questionnaire called "Oral Health for Parents" were used to evaluate oral hygiene in children. From the analysis of the results, it’s highlighted that the aforementioned program should be considered in prevention and promotion of oral health, since it promotes optimal knowledge in the adult population that was evident in the oral health of children under 5 years of age at the end of the intervention. It’s concluded that an educational program on prevention in oral health improves the level of knowledge of parents about the oral health of their children, reducing bacterial plaque in children, evidenced by a positive index of oral hygiene after the intervention.